On the Axis of Psychosomatic Totality - Lutz Goetzmann; Adrian Siegel; Barbara Ruettner (EJP import test, 2020)
Summary: The model of an “axis of psychosomatic totality” is proposed in order to understand psychosomatic symptoms. Basically, the axis runs between the symbolic and the asymbolic poles I and II: symptoms which represent an unconscious fantasy can be assigned to the symbolic pole. Bodily symptoms resulting from a regressive or reversible somatization are located on the asymbolic pole I; bodily illnesses that manifest as organ lesions resulting from a progressive somatization and which potentially lead to death, on the asymbolic pole II. The symbolic and asymbolic poles are subject to defence (repression, splitting, foreclosure). Conversion takes place at all poles, induced by the associated excitation of anxiety. Symptoms on the middle section of this axis (imaginary zone) are early mirror effects combining bodily and emotional experience. We place these considerations in the context of the Lacanian concept that the subjective world is composed of the Real, Imaginary and Symbolic. Moreover, we develop the idea of the psychosomatic symptom as a sinthome, which we classify as bolted, white, or breathing. The paper concludes with references to the therapeutic approaches.
Keywords: Axis of Psychosomatic Totality; conversion; Sinthome; Somatization; Symbolic pole; symbolization; Symptom